Analysis of factors influencing energy-saving advantages of outside and inside insulation of exterior walls in intermittent air-conditioned buildings - Liting Yuan; Zhiyi Wang; Xiaodong Zhu; Yuxin Wu; Haijiao Cui (Case Studies in Thermal Engineering, 2023)
An effective approach to reducing building energy is determining the proper insulation location of the exterior walls. Two conflicting conclusions were found in previous research that focused on the optimal insulation location of exterior walls in buildings with intermittently operated convective air systems (CASs). Why conflicting conclusions are produced and which factors influence them have not yet been answered. Thus, this paper analyzes the generation of the transmission load through the exterior walls with outside and inside insulation, and accordingly evaluates the parameters that might affect the energy-saving advantage of two insulation locations. An analytic model is utilized to calculate the heat transfer through the exterior walls. Results show that the heat stored in exterior walls’ inner layer during CAS off-periods is the key to determining the relative energy-saving of two insulation locations. Furthermore, the relative energy-saving increases with thermal capacity of exterior envelopes and air change rate but decreases with the increase in thermal capacity of interior envelopes and setpoint temperature. Based on these, a predictive model is devised to determine the proper insulation location of exterior wall. A critical daily sol-air temperature range beyond which the relative energy-saving advantage transitions is found using the model.